Postnatal quality of life in women after normal vaginal delivery and caesarean section - Kazemnejad Anoshirvan; Lamyian Minoor; Parsay Sousan; Torkan Behnaz; Montazeri Ali (BMC, 2009)
Abstract Background Caesarean section might increase the incidence of surgical interventions and problems resulting from hospitalization and thus affecting quality of life in women after delivery. This study aimed to compare quality of life in women after normal delivery and caesarean section. Methods This was a prospective study. A sample of women with normal delivery and caesarean section from 5 health care centers in Isfahan, Iran were entered into the study. Quality of life was measured using the SF-36 at two points in time (time 1: 6 to 8 weeks after delivery; time 2: 12 to 14 weeks after delivery). Data were analyzed to compare quality of life in the two study groups. Results In all 100 women were interviewed (50 with normal delivery and 50 with caesarean section). Postnatal quality of life in both groups was improved from time1 to time 2. However, comparing the mean scores between the normal and caesarean delivery groups the results showed that in general the normal vaginal delivery group had a better quality of life for almost all subscales in both assessment times. The differences were significant for vitality (mean score 62.9 vs. 54.4 P = 0.03) and mental health (mean score 75.1 vs. 66.7, P = 0.03) at first assessment and for physical functioning (mean score 88.4 vs. 81.5, P = 0.03) at second evaluation. However, comparing the findings within each group the analysis showed that the normal vaginal delivery group improved more on physical health related quality of life while the caesarean section group improved more on mental health related quality of life. Conclusion Although the study did not show a clear cut benefit in favor of either methods of delivery that are normal vaginal delivery or caesarean section, the findings suggest that normal vaginal delivery might lead to a better quality of life especially resulting in a superior physical health. Indeed in the absence of medical indications normal vaginal delivery might be better to be considered as the first priority in term pregnancy.